PENERAPAN PENDEKATAN TARL BERBANTUAN MEDIA GEOBOARD UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA KELAS V SDN JEMBERLOR O5 - Fatkur, Mujib; Galuh Melinda Safitri, Aprillia Putri Pratiwi; Kuntari Dwi Meitikosari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low mathematics learning outcomes of students in mathematics subjects. The TaRL approach is considered appropriate to use because it emphasizes the adjustment of the level of difficulty of the material with the initial abilities of students. Geoboard media is considered appropriate to use in mathematics subjects on the characteristics of flat shapes because it helps in understanding abstract concepts through real objects. The purpose of this study was to improve the learning outcomes of grade VA students of SDN Jember Lor 05 in Mathematics subjects through the TaRL approach assisted by Geoboard media. The method used was Classroom Action Research (CAR) with the Kemmis and MC Tagart models with two cycles. The results of the study showed an increase in the percentage of student learning outcomes completion from the pre-cycle 28% who achieved completion. After the intervention, student completion increased to 57% in the first cycle and 85% in the second cycle. So it can be concluded that the TaRL approach is effective in improving student learning outcomes.